2013
DOI: 10.3389/fnbeh.2013.00112
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cortical c-Fos and Zif-268 Expression after Object and Spatial Memory Processing in a Standard or Episodic-Like Object Recognition Task

Abstract: Episodic memory reflects the capacity to recollect what, where, and when a specific event happened in an integrative manner. Animal studies have suggested that the medial temporal lobe and the medial pre-frontal cortex are important for episodic-like memory (ELM) formation. The goal of present study was to evaluate whether there are different patterns of expression of the immediate early genes c-Fos and Zif-268 in these cortical areas after rats are exposed to object recognition (OR) tasks with different cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 62 publications
(125 reference statements)
8
37
0
Order By: Relevance
“…Interestingly, using early-gene activation techniques, Barbosa and co-workers analysed the correlation between cognitive demand in object recognition variants (discrimination between novel and familiar object and spatiotemporal discrimination of familiar object) and activation of the mPFC including the ACgx. They found that the number of c-Fos and Zif-268-positive neurons in the mPFC was significantly increased compared with the control condition after retrieval of a NOR task (Barbosa et al 2013). These data suggest that activity within the mPFC is associated with successful retrieval of NOR.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, using early-gene activation techniques, Barbosa and co-workers analysed the correlation between cognitive demand in object recognition variants (discrimination between novel and familiar object and spatiotemporal discrimination of familiar object) and activation of the mPFC including the ACgx. They found that the number of c-Fos and Zif-268-positive neurons in the mPFC was significantly increased compared with the control condition after retrieval of a NOR task (Barbosa et al 2013). These data suggest that activity within the mPFC is associated with successful retrieval of NOR.…”
Section: Discussionmentioning
confidence: 95%
“…Since Zif-268 levels in the hippocampus are increased 1-2 h after a novel stimulus (Barbosa et al, 2013), we believe that a 6 h increase in vehicle-injected animals could be related to a second wave of Zif-268 transcription and translation. This re-induction is probably related to the occurrence of REM sleep in vehicleinjected animals, but not in haloperidol-injected animals, during the 4 h interval following object exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Animal studies have to our knowledge never evaluated neural network recruitment in episodic-like memory, and in investigations of other forms of memories, distinct patterns of expression of different IEGs were often observed (Tse et al, 2011;Barbosa et al, 2013), probably because these IEGs have different functions (Davis et al, 2003). c-Fos is generally believed to reflect eventinduced neuronal activation, while the transcription factor Zif268 more likely reflects synaptic activation and plasticity mechanisms involved in long-term memory (Jones et al, 2001;Veyrac et al, 2014).…”
Section: Discussionmentioning
confidence: 99%